GENERALIZED GAMMA REGRESSION FOR ANALYZING ALCOHOL CONSUMPTION SURVIVABILITY - Murti, Fadhaa Aditya Kautsar (Jurnal Biometrika dan Kependudukan, 2024)
Alcohol consumption remains a public health problem, affecting various organ systems. Its impact can be detrimental to adolescents, leading to disturbed social and economic development. Gender differences exist, with male adolescents being more affected. This research aims to understand alcohol consumption among male adolescents in Indonesia. This study used pseudo longitudinal data from the 2017 Indonesian Demographic Health Survey (IDHS) and employed a survival analysis method using the generalized gamma approach. A total of 12,373 (weighted) adolescents were analyzed, with 4,573 of them classified as events. A time ratio (TR) was reported. Smoking was identified as the most substantial variable, shortening the survivability of alcohol consumption by 19%. Additionally, living in rural areas, having tried drugs, and having had sex were identified as risk factors, while education level and mobile phone ownership were protective factors. Risk behaviors shorten alcohol consumption survival among adolescents. Cross-sectoral interventions and comprehensive counseling are essential for effective prevention.